2020
DOI: 10.1038/s41598-020-59116-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological significance of endoplasmic reticulum stress proteins in ovarian carcinoma

Abstract: Epithelial ovarian cancer (EOC) is a leading cause of cancer-related mortality in the United States due to the late-stage disease at diagnosis. Overexpression of GRP78 and PDI following endoplasmic reticulum (ER) stress and activation of the unfolded protein response (UPR) promote growth and invasion in cancer. To identify novel prognostic biomarkers in EOC, here we determined the expression of ER stress-associated proteins (GRP78, ATF6 and PERK) and correlated with clinical outcome in EOC. Tissue microarray (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…In EOC, GRP78, ATF6α and PERK were highly expressed in EOC tissues compared to the normal tissues, and correlated with advanced tumor stages. Moreover, high expression of GRP78 predicted poor overall survival (OS), suggesting that expression of UPR-associated proteins could be prognostic biomarkers in ovarian cancer [32]. Our study found that knockdown of CREBBP decreased GRP78 expression, suggesting low expression of CBP was correlated with good prognosis in ovarian cancer, which was in accordance with the results generated from the Kaplan-Meier Plotter database (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In EOC, GRP78, ATF6α and PERK were highly expressed in EOC tissues compared to the normal tissues, and correlated with advanced tumor stages. Moreover, high expression of GRP78 predicted poor overall survival (OS), suggesting that expression of UPR-associated proteins could be prognostic biomarkers in ovarian cancer [32]. Our study found that knockdown of CREBBP decreased GRP78 expression, suggesting low expression of CBP was correlated with good prognosis in ovarian cancer, which was in accordance with the results generated from the Kaplan-Meier Plotter database (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Emerging evidence showed that activation of UPR signaling contributed to tumor development and was correlated with unfavorable prognosis in cancer patients 31 , 32 . In EOC, GRP78, ATF6α and PERK were highly expressed in EOC tissues compared to the normal tissues, and correlated with advanced tumor stages.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the major pro-survival role of ATF6, its expression level has been shown to be significantly upregulated in various cancer types [63][64][65][66]. Higher expression level of ATF6 has been closely correlated with cancer metastasis and recurrence [67,68] and served as a prognostic indicator of cancer [69].…”
Section: Atf6α Pathwaymentioning
confidence: 99%
“…Therefore, it is not surprising that hypoxia-dependent signaling pathways are commonly de-regulated in cancer cells. A recent study demonstrated that clear cell and serous EOC are under constant endoplasmic reticulum (ER) stress caused by the accumulation of unfolded proteins; due to this, the unfolded protein response (UPR) sensor PERK located in the ER activates and phosphorylates the eukaryotic translation initiation factor eIF2, resulting in a general suppression of translational initiation and global protein synthesis [ 117 ].…”
Section: Functional Pathways Affected By Oc Fitness Genesmentioning
confidence: 99%